Features on cardiac magnetic resonance imaging and accuracy of echocardiographic findings for diagnosing constrictive pericarditis - Iqbal, Salik ur Rehman; Fateh Ali Tipoo Sultan (Journal of the Pakistan Medical Association, 2021)
Constrictive pericarditis is a rare disease with a difficult diagnosis. Cardiac magnetic resonance (CMR) imaging data of Aga Khan University Hospital, from January 2011 to March 2020 was retrospectively reviewed and patients with the diagnosis of constrictive pericarditis were included. A total of 22 patients were included with the mean age of 46 + 16 years and majority (77%, n=17) being male. The most common findings on transthoracic echo were significant respiratory variation in mitral and tricuspid inflow velocities (91%, n=20) and septal annular e’>9 (86%, n=19). Most common finding on CMR was respiratory septal shift in 100% (n=22) followed by septal bounce in 95% (n=21), and thickened pericardium in 82% (n=18). Nearly two-third patients (n=15) were considered for pericardiectomy but it was deferred in 5 patients due to high surgical risk. Ten patients underwent pericardiectomy with no mortality on a mean follow up of 4 + 2 years. Continuous...